Impact of Tahfidz Learning Management and Learning Environment on Tahfidz Learning Motivation among Madrasah Tsanawiyah Students - Alfiandrizal Alfiandrizal; Junaidi Junaidi; Muhammad Afif Al Faruq; Kunalan Kuriaya (At-Ta'lim : Media Informasi Pendidikan Islam, 2025)
ENGLISH: Impact of Tahfidz Learning Management and Learning Environment on Tahfidz Learning Motivation among Madrasah Tsanawiyah StudentsObjective: This study aims to determine the effect of Tahfidz learning management and learning environment on students' motivation to learn Tahfidz at MTsN 2 Agam. Method: This study employs a quantitative method, utilizing multiple regression analysis, to investigate the relationship and effect between variables. Results: The TAHFIDZ learning management system has a significant effect on student learning motivation, such that the better the planning, implementation, and evaluation of Tahfidz, the higher the students' motivation in memorizing the Qur'an. Conclusion: Both variables, Tahfidz learning management and learning environment, have an essential contribution in increasing student learning motivation. Contribution: This study provides input for teachers, madrasahs, and policymakers to enhance the management of Tahfidz programs and create a more supportive learning environment, thereby improving the quality of students' memorization.INDONESIAN: Pengaruh Manajemen Pembelajaran Tahfidz dan Lingkungan Belajar terhadap Motivasi Belajar Tahfidz Siswa Madrasah Tsanawiyah Tujuan: Penelitian ini bertujuan untuk mengetahuipengaruh manajemen pembelajaran tahfidz dan lingkungan belajar terhadap motivasi belajar tahfidz siswa di MTsN 2 Agam. Metode: Penelitian ini menggunakan metode kuantitatif dengan teknik analisis regresi berganda untuk mengetahui hubungan dan pengaruh antarvariabel. Hasil: Manajemen pembelajaran tahfidz berpengaruh signifikan terhadap motivasi belajar siswa, sehingga semakin baik perencanaan, pelaksanaan, dan evaluasi tahfidz, semakin tinggi motivasi siswa dalam menghafal Al-Qur’an. Kesimpulan: Kedua variabel, baik manajemen pembelajaran tahfidz maupun lingkungan belajar, memiliki kontribusi penting dalam meningkatkan motivasi belajar siswa. Kontribusi: Penelitian ini memberikan masukan bagi guru, madrasah, dan pemangku kebijakan untuk memperbaiki pengelolaan program tahfidz dan menciptakan lingkungan belajar yang lebih mendukung demi peningkatan kualitas hafalan siswa.